2020
DOI: 10.1136/jnnp-2020-323992
|View full text |Cite
|
Sign up to set email alerts
|

Autologous haematopoietic stem cell transplantation compared with alemtuzumab for relapsing–remitting multiple sclerosis: an observational study

Abstract: ObjectiveTo compare outcomes after treatment with autologous haematopoietic stem cell transplantation (AHSCT) and alemtuzumab (ALZ) in patients with relapsing–remitting multiple sclerosis.MethodsPatients treated with AHSCT (n=69) received a conditioning regimen of cyclophosphamide (200 mg/kg) and rabbit anti-thymocyte globulinerG (6.0 mg/kg). Patients treated with ALZ (n=75) received a dose of 60 mg over 5 days, a repeated dose of 36 mg over 3 days after 1 year and then as needed. Follow-up visits with assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 31 publications
1
57
0
4
Order By: Relevance
“…Of the 6 included primary studies, 2 were RCTs 16,17 and 4 were retrospective cohort studies. [18][19][20][21] Both RCTs (1 phase III 16 and 1 phase II 17 ) were open-label, multi-centre, parallel, 1:1 trials. Both reported sample size calculations to detect a clinically relevant treatment effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 6 included primary studies, 2 were RCTs 16,17 and 4 were retrospective cohort studies. [18][19][20][21] Both RCTs (1 phase III 16 and 1 phase II 17 ) were open-label, multi-centre, parallel, 1:1 trials. Both reported sample size calculations to detect a clinically relevant treatment effect.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed characteristics of the included primary studies [16][17][18][19][20][21] (Table 2) and the European Society for Blood and Marrow Transplantation (EBMT) guideline 12 and the American Society for Blood and Marrow Transplantation (ASBMT) 22 guideline (Table 3) are presented in Appendix 2.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
“…On the recommendations of groups such as the (United States) National Multiple Sclerosis Society (Miller et al, 2021) and European Society for Blood and Marrow Transplantation (Sharrack et al, 2020), autologous HSCT may be beneficial for the treatment of active RRMS that is refractive to current DMTs (or in cases wherein these are contraindicated). Indeed, some appraisals suggests that HSCT may represent a cost-effective alternative to DMTs for the treatment of RRMS (Burt et al, 2020), however, larger studies are ongoing to ascertain whether HSCT is truly advantageous to current best standards of care [e.g., (Burt et al, 2019;Zhukovsky et al, 2021), and the BEAT-MS trial, NCT04047628]. While promising for the treatment of RRMS, the weight of clinical evidence suggests that autologous HSCT has limited efficacy in treating chronic PMS without superimposed disease activity (Bowen et al, 2012;Miller et al, 2021).…”
Section: Clinical Evidence For Hscs In Pmsmentioning
confidence: 99%
“…The MS International Stem Cell Transplant (MIST)-trial (NCT00273364) demonstrated the superiority of AHSCT versus DMTs in terms of the time to disease progression [ 43 ]. More recently, an observational cohort study compared outcomes after treatment with alemtuzumab and AHSCT and found that the chance of maintaining NEDA was significantly higher in the AHSCT-treated group [ 44 ]. Several clinical trials, comparing the effects of AHSCT with high efficacy DMTs in patients with active RRMS, are ongoing ( Table 1 ).…”
Section: Cell Therapy Approaches For the Treatment Of Multiple Sclerosismentioning
confidence: 99%